The Role of Personal Archival Management in Enhancing Public Archival Awareness - Nafiisah Famela Kurniasari; Fani Tri Yuliyanti; Nunung Aliyati Fajer (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to analyze the role of personal archival management in enhancing public archival awareness. The main issue addressed in this research is the low level of public archival awareness and the suboptimal practice of personal archival management, which often results in administrative difficulties, document loss, and inefficiencies in accessing information. This study employs a conceptual literature review approach by examining various scientific publications, archival regulations, and previous studies related to personal archives, archival literacy, and public archival awareness. The findings indicate that personal archival management plays a significant role in supporting administrative effectiveness and shaping archival awareness within society. However, the implementation of systematic personal archival management remains limited due to low archival literacy, lack of orderly administrative habits, and limited digital literacy. In addition, efforts to enhance public archival awareness require adaptive strategies, including digital-based archival education and active community participation. This study also highlights that effective personal archival management can reduce administrative barriers and strengthen public understanding of the value and function of archives in everyday life. The study concludes that personal archival management is a key factor in enhancing public archival awareness and in supporting the development of a sustainable archival culture in society.